Report on Sustainable Soil Management Practices in Dry Areas: Morocco case study - Moussadek, Rachid; Iaaich, Hamza (International Center for Agricultural Research in the Dry Areas, 2022)
Sustainable soil management practices (SSMP) render multifaceted benefits to meet the SDG goals, whereas its implication for climate change mitigation is significant. Sustainable soil management combines technologies, policies, and activities aiming at improving productivity, reducing the level of production risk (security), protecting the potential of natural resources and preventing soil degradation and water quality (protection), economic viability, and socially acceptable. The world's climate continues to change at rates that are projected to be unprecedented in recent human history. The Intergovernmental Panel on Climate Change (IPCC) assessment reports suggest a global increase in average surface temperature between 1.4 and 5.8°C from 2000 to 2100. Sustainable soil management practices can minimize the negative effect of climate change. Depending on soil types, cropping practices and the climate, soil can contribute to or slow down climate change. Knowing about good conservation management practices and focusing on other innovative farming practices used in conservation agriculture or agroforestry is important. This is to make the best use of the soil's regulatory capacity. On the other hand, good soil management practices can be adopted as part of the new ecological services policies and thus promote agricultural strategies for adaptation to climate change.